2013
DOI: 10.32398/cjhp.v11i1.1521
|View full text |Cite
|
Sign up to set email alerts
|

Examination of a Peer-Led, Non-Diet Nutrition and Exercise Adherence Pilot Program on a College Campus

Abstract: A non-equivalent control group design was utilized to investigate the effect of a non-diet, peer-led, tailored nutrition and exercise adherence intervention (FitU) on exercise stages of change, intuitive eating, and barriers to healthy eating and exercise in college females. Female students (n=17) who enrolled in the 8-10 week program served as the intervention group and general education students who did not receive an intervention served as the control group (n=16). Surveys were administered pre and post int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…2,3,36,55,57,63,66,69 Of these, 1 reported a significant reduction in body image avoidance, 2,3 although the reduction was not maintained at 2-year follow-up, whereas 1 reported a non-significant reduction. 66 Two studies reported a significant reduction in body image dissatisfaction, 2,3,57 1 reported a non-significant reduction, 66 and 1 reported no change.…”
Section: Overview Of Studiesmentioning
confidence: 58%
See 4 more Smart Citations
“…2,3,36,55,57,63,66,69 Of these, 1 reported a significant reduction in body image avoidance, 2,3 although the reduction was not maintained at 2-year follow-up, whereas 1 reported a non-significant reduction. 66 Two studies reported a significant reduction in body image dissatisfaction, 2,3,57 1 reported a non-significant reduction, 66 and 1 reported no change.…”
Section: Overview Of Studiesmentioning
confidence: 58%
“…2,3,58,59,62,63,[65][66][67]69 One study re-ported significant increases in energy expenditure from pre-to postintervention compared with controls. 2, 3 Carroll and colleagues 69 were the only researchers to obtain post data from most participants to measure changes in fitness levels from pre to post.…”
Section: Overview Of Studiesmentioning
confidence: 96%
See 3 more Smart Citations